A survey of commercially available electronic hand hygiene monitoring systems and their impact on reducing healthcare-associated infections. (May 2021) - Cawthorne, K-R.; Cooke, R.P.D.
Summary: Background: Although the benefits of electronic hand hygiene monitoring systems (EHHMSs) are well described, uptake has been poor since they were first introduced over 10 years ago. There is considerable published evidence on the association between the introduction of EHHMSs and improved hand hygiene (HH) compliance rates. However, their impact on healthcare-associated infection (HCAI) reduction is much less clear-cut. Methods: Commercial EHHMS identification was undertaken using a Google internet search and all relevant websites and marketing materials were reviewed. A structured literature search was undertaken to identify evidence of HCAI reduction through EHHMS implementation. Structured interviews were undertaken with a number of Directors of Infection Prevention and Control (DIPCs) from acute NHS Trusts in the North West of England to seek opinions on HH improvement strategies and the use of EHHMSs. Results: Twenty-nine commercial EHHMSs were identified, 20 of which are currently market active. Six EHHMSs had supporting evidence, across nine published studies, demonstrating their ability to reduce HCAIs. However, most evaluation designs were quasi-experimental with only one study using a high-quality stepped-wedge cluster randomized controlled trial design. In this study the EHHMS was part of a wider HH multi-modal improvement strategy. Structured interviews were undertaken with five DIPCs who consistently expressed a reluctance to support financial investment into this type of technology until EHHMS cost-effectiveness was better established. Conclusions: The evidence base for the ability of EHHMSs to reduce HCAIs needs to improve before NHS trusts will consider procuring them.